Prognostic impact of bone invasion in canine oral malignant melanoma treated by surgery and anti‐CSPG4 vaccination: A retrospective study on 68 cases (2010–2020). (6th September 2021) - Camerino, Mariateresa; Giacobino, Davide; Manassero, Luca; Iussich, Selina; Riccardo, Federica; Cavallo, Federica; Tarone, Lidia; Olimpo, Matteo; Lardone, Elena; Martano, Marina; Del Magno, Sara; Buracco, Paolo; et al.
Abstract: Prognosis of canine oral malignant melanoma encompasses clinical, histological and immunohistochemical parameters. The aim of this study was to evaluate the prognostic impact of bone invasion in oral canine melanoma. Sixty‐eight dogs bearing oral melanoma staged II and III that underwent surgery and anti‐CSPG4 electrovaccination, with available histological data and a minimum follow up of minimum 1 year, were retrospectively selected. Bone invasion was detected on imaging and/or histology. Median survival time of dogs with evidence of bone invasion (group 1) was 397 days and significantly shorter compared with dogs with oral melanomas not invading the bone (group 2, 1063 days). Dogs with tumours localised at the level of the cheek, lip, tongue and soft palate (soft tissue ‐ group 3) lived significantly longer compared with dogs having tumours within the gingiva of the maxilla or mandible (hard tissue ‐ group 4) with a median survival time of 1063 and 470 days, respectively. Within group 4, the subgroup of dogs with tumours not invading the bone (group 5) showed a significant prolonged survival time (972 days) in comparison with dogs of group 1 (bone invasion group). Similar results were obtained for the disease‐free intervals amongst the different groups. Statistical analysis showed that Ki67 and mitotic count were correlated with shorter survival in patients of group 1 (with bone invasion). Bone invasion should always be assessed since it appears to be a negative prognostic factor.